Lactate acid level and prognosis of neonatal necrotizing enterocolitis: a retrospective cohort study based on pediatric-specific critical care database - Yuting Wang; Lifei Lai; Qi Zhang; Lei Zheng (Elsevier, 2023)
Objective: To investigate the relationship between lactate acid level and hospitalization mortality in neonatal necrotizing enterocolitis (NEC). Method: Paediatric-specific critical care database collected clinical data from the intensive care unit of Children's Hospital Affiliated to Zhejiang University Medical College from 2010 to 2018. Clinical and laboratory examination information of NEC patients was collected and divided into the death group and discharge group to find out the risk factors affecting the prognosis through univariate and multivariate analysis. Results: Among 104 NEC neonates, the admission age was 7.5 days and the weight was 2.03 kg. Comparing the death group with the discharge group, there were significant differences in therapeutic regimen, pH, serum albumin, total protein, creatinine and lactate acid. Multivariate and threshold effect analysis showed that lactate acid had a linear correlation with hospital mortality, and newborns who died in the hospital had much higher lactate levels than those who were discharged. The mortality of NEC newborns increased by 40-45% for every 1 mmol/L increase in lactate acid level. Conclusions: There was a correlation between lactate acid level and hospital mortality in newborns with NEC, and lactate acid level was an important index to evaluate the prognosis of NEC.